Breath‐print analysis by e‐nose may refine risk stratification for adverse outcomes in cirrhotic patients. (21st August 2016) - De Vincentis, Antonio; Pennazza, Giorgio; Santonico, Marco; Vespasiani‐Gentilucci, Umberto; Galati, Giovanni; Gallo, Paolo; Zompanti, Alessandro; Pedone, Claudio; Antonelli Incalzi, Raffaele; Picardi, Antonio
Abstract: Background & Aims: The spectrum of volatile organic compounds in the exhaled breath (breath‐print, BP) has been shown to characterize patients with cirrhosis and with worse hepatic function. However, the association of different BPs with clinically relevant outcomes has not been described yet. Hence, we aimed to evaluate the association between BPs, mortality and hospitalization in cirrhotic patients and to compare it with that of the "classical" prognostic indices (Child‐Pugh Classification [CPC] and MELD). Methods: Eighty‐nine cirrhotic patients (M/F 59/30, mean age 64.8 ± 11.3, CPC A/B/C 37/33/19) were recruited and followed up for a median time of 23 months. Clinical and biochemical data were collected. Breath collection and analysis were obtained through Pneumopipe ® and BIONOTE e‐nose respectively. Results: Four different BP clusters (A, B, C, D) were identified. BP clusters A and D were associated with a significantly increased risk of mortality (HR 2.9, 95% confidence intervals [CI] 1.5–5.6) and hospitalization (HR 2.6, 95% CI 1.4–4.6), even in multiple adjusted models including CPC and MELD score (adjusted [a]HR 2.8, 95% CI 1.1–7.0 for mortality and aHR 2.2, 95% CI 1.1–4.2 for hospitalization). CPC C maintained the strongest association with both mortality (aHR 17.6, 95% CI 1.8–174.0) and hospitalization (aHR 12.4, 95% CI 2.0–75.8). Conclusions: This pilot study demonstrates that BP clusters are associated with significant clinical endpoints (mortality and hospitalization) even independently from "classical" prognostic indices. Even though further studies are warranted on this topic, our findings suggest that the e‐nose may become an adjunctive aid to stratify the risk of adverse outcomes in cirrhotic patients.